Удосконалення системи адміністрування у сфері природокористування - Martienko, Antonina; Khumarova, Nina (Dr. Viktor Koval, 2017)
Introduction. The main content of modern trends in the rational use of natural resources is aimed at reducing all types of resource flows per unit of produced products or services at different levels of economic activity and minimizing the generation of waste per unit produced national product. The rational use of natural resources directly depends on the development of the permit system, reducing the scale of material and resource flows of economic activity. Aim and tasks. The purpose of the article is to substantiate the main directions of improvement of the administrative system in the field of licensing services of nature use, as an instrument for promoting the process of transition to environmental friendly technologies and reducing the resource intensity of production. Research results. The article outlines directions for improving the administration of licensing services in the field of nature management, taking into account the need to reduce the volume of material and resource intensities of economic activity. It is substantiated that it is not necessary to approach this procedure formally when issuing permits for the use of natural resources (based on the emissions during the operation of this equipment) and taking into account such factors as existing of ecologically clean technologies, the assimilation potential of the territory, the existing environmental burden and external effects. When administering the permitting system in the environment, it is necessary to create a separate structural subdivision at the Centre of administrative services. Also, it is necessary to establish an electronic document flow between the licensing and administrative centres, the subject of the use of natural resources and organizations authorized to issue permits for handling natural resources, and the creation of a unified database, contained and gathered information from the "History of the use of natural resources for a business entity". Information of this document should help to make influential decisions such as the directions of natural resources use, a system for monitoring their use, and the basis for the revocation of the permit in case of non-fulfilment of its conditions. Conclusions. The permit system in environmental use should be aimed at preserving the environment, taking into account the interests of producers of goods and services, their consumers and third parties living or staying in the region. The system for obtaining permits for the use of natural resources and for emissions into the atmosphere, discharges into water facilities and the placement of wastes in the natural environment should be, on the one hand, simplified and exempt from corruption mechanisms, and on the other hand, simplified and accessible to the subjects of their obtaining.